2019
DOI: 10.1177/1532708619884958
|View full text |Cite
|
Sign up to set email alerts
|

Found Poetry: Reimagining What is Present and What is Absent Through the Journals of Her Life

Abstract: This article maps an emergent qualitative research process of writing found poetry to give voice to a long-term care patient who was slowly losing her physical capabilities to supra nuclear palsy. Through an initial chance encounter, the poem Thank you was written from the patient’s scribed journals and then performed in variety of settings for a variety of audiences. First, an academic conference proceeding, followed by a video recording performance, and finally, it was performed for health care providers at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…My reflexive exercise in the doctoral class had a transformative impact on me [51][52][53][54][55]. It helped me to discover my true selfhood and to explore the qualitative inquiry approach.…”
Section: Discussionmentioning
confidence: 99%
“…My reflexive exercise in the doctoral class had a transformative impact on me [51][52][53][54][55]. It helped me to discover my true selfhood and to explore the qualitative inquiry approach.…”
Section: Discussionmentioning
confidence: 99%
“…The methods involved in creating the found poem were informed by qualitative researchers in the medical humanities [ 9 , 11 , [22] , [23] , [24] ]. The first author, a health science researcher with experience in the context of cancer, PTG, and conducting research with SGM communities, also has experience writing and publishing poetry.…”
Section: Methodsmentioning
confidence: 99%
“…Aligned with Brown (2020), who suggested that found poetry should entail choosing words and phrases repeated throughout the text [ 23 ], the first author then re-read the word processing document while highlighting similar concepts, words, and imagery. The highlighted text was exported into a new word-processing document.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, self-reflexivity is elusive as it includes positioning oneself in a topic while navigating past experiences, present perspectives, and possibilities of what lies ahead. It is in the “space of knowing and not knowing” (Brown, 2020, p. 7), where poetry exposes this temporal continuum through emotions. Furthermore, as emotions are fundamental to the coping process (Folkman & Moskowitz, 2004), exploring emotions through self-reflexive poetry offers space to cope with stressors and/or crises.…”
Section: Reflections On Methodologymentioning
confidence: 99%